The Relationship of Emotional Intelligence and Breastfeeding Self-Efficacy in Mothers in the Early Postpartum Period - Karakoc, Hediye; Mucuk, Ozlem; Ozkan, Hava (Mary Ann Liebert, Inc, 2020)
Introduction: Women have widespread breastfeeding problems in postpartum period. Emotional intelligence (EI) is thought to be important in problem-solving related to breastfeeding. Research Aims: The study was conducted to investigate the correlation between the EI and breastfeeding self-efficacy (BFSE) of women in the early postpartum period and the associated factors. Materials and Methods: A cross-sectional study was conducted in cesarean-postpartum service of a hospital in Erzurum between May 2015 and May 2016. The sample of the study consisted of 271 women. The dependent variables constituted the EI and BFSE mean scores. Descriptive statistics, independent samples t tests, one-way analysis of variance, Kruskal-Wallis test, Mann-Whitney U test, and Pearson correlation analysis were used. Results: The age, education level, perceived income status, and the status of planned pregnancy of the mothers affected their EI mean score, whereas their residence place, income status, the number of pregnancy and living children, and status of receiving prenatal care affected their BFSE levels. No significant correlation was found between the EI and BFSE mean scores in the early postpartum period (r = 0.77, p = 0.207). Conclusions: No significant correlation was determined between the EI and BFSE in the early postpartum period.
Keywords: postpartum period; emotional intelligence; breastfeeding self-efficacy